PELAKSANAAN SISTEM INFORMASI MANAJEMEN (SIM) DALAM PENGAMBILAN KEPUTUSAN DI DEWAN DAKWAH ISLAMIAH INDONESIA (DDII) PROVINSI LAMPUNG - Sri Ilham Nasution, Rini Setiawati, (Universitas Islam Negeri Raden Intan Lampung, 2019)
The problem in this study is how the implementation and role of the management information systems in decision making in the Islamic Board of Islamic Da'wah of Indonesia in Lampung. Data collection was carried out in three ways: interviews, observations and documentation. Data analysis used is an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of management information systems in decision making in the Islamic Da'wah Board of Indonesia in Lampung Province is first, a computer-based management information system in which all records and documents can be stored neatly in a computer system and if needed in an easier search because only by searching for the file name, the required archive will be displayed. Second, decision making based on the principle of consensus agreement. While the role of management information systems in decision making in the Indonesian Islamic Da'wah Council of Lampung Province is to facilitate leaders in making decisions because the information needed is available, as a material for decision making, as an alternative action in decision making and material for reviewing strategy and organizational plans.